INTEGRASI ETIKA ISLAM DAN PENDIDIKAN KARAKTER HUMANIS DI SEKOLAH ISLAM DALAM MERESPON KRISIS SOSIAL (Studi Kasus Pada SDIT Alam Nurul Islam Dua Ngawi) - Darmanto (LPPM STAI Muhammadiyah Probolinggo, 2026)
This research is motivated by the social crisis that has gripped society, such as increasing intolerance, individualism, and the moral decline of the younger generation. This demands an educational model capable of harmoniously integrating religious and humanitarian values. SDIT Alam Nurul Islam Dua Ngawi is an educational institution that strives to implement the integration of Islamic ethics and humanist character education in its learning process. This research uses a qualitative approach with a case study method. Data were collected through participatory observation, in-depth interviews, and documentation of various school activities. Data analysis was conducted descriptively through the processes of reduction, presentation, and drawing conclusions. The results show that SDIT Alam Nurul Islam Dua Ngawi has successfully integrated Islamic ethical values and humanist character through integrative thematic learning, the cultivation of noble morals, and the creation of a friendly, inclusive, and reflective school culture. Values such as honesty, responsibility, empathy, discipline, cooperation, and love for the environment are instilled through experience-based activities and teacher role models. The integration of Islamic ethics and humanist character education has proven effective in shaping students who are both religious and humanist. This strategy not only strengthens students' personal character but also fosters social awareness as part of a broader community. These findings contribute to the development of an Islamic values-based character education model that is adaptive to social dynamics and relevant to the challenges of 21st-century education.